2022
DOI: 10.1002/app.52891
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyimide aerogels by freeze‐extraction and chemical imidization for 3D printing

Abstract: Polyimide (PI) aerogels with excellent mechanical and thermal stability, low density, and flexibility have attracted extensive attention in recent years. However, the existing preparation method usually requires chemical pre‐crosslinking followed by supercritical drying or freeze drying, and then thermal imidization, which has the weakness of a complicated preparation method and high cost. In this study, PI aerogels were prepared by a simple method that involved freeze extraction and chemical imidization, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As a result, the printed polyimide structures were inconsistent with cast aerogels: the printed aerogel pores were on the micron scale, whereas cast aerogels had nanoscale porosity. Other approaches to DIW of pure polyimide aerogels have harnessed additional processing steps such as ball milling 88 or post-printing imidization by chemical treatment, 46 heating, or ultraviolet light exposure. 89 The process of directly printing polyimide sol using an off-the-shelf printing setup is critical to expanding the applications of these important materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the printed polyimide structures were inconsistent with cast aerogels: the printed aerogel pores were on the micron scale, whereas cast aerogels had nanoscale porosity. Other approaches to DIW of pure polyimide aerogels have harnessed additional processing steps such as ball milling 88 or post-printing imidization by chemical treatment, 46 heating, or ultraviolet light exposure. 89 The process of directly printing polyimide sol using an off-the-shelf printing setup is critical to expanding the applications of these important materials.…”
Section: Introductionmentioning
confidence: 99%
“…2 Primary drying methods include critical point drying or freeze drying, although some studies have demonstrated ambient pressure drying by strengthening the nanostructure 28,29 or modifying the surface to enable the nanostructure to "spring back" after drying. 1,2,[30][31][32] Aerogels have a diverse array of compositions, including silica, 1,13,20,22,[30][31][32] titania, 33 and other metal oxides, [34][35][36] along with carbon, 17,[37][38][39][40][41] chalcogenides, [42][43][44][45] polymers, 4,5,8,26,[46][47][48][49][50] and biological materials. 10,[51][52][53][54] Of these, polymer aerogels offer unique opportunities to tailor chemical composition, with polyimide aerogels being of particular interest due to their combination of good mechanical performance and high thermal stability.…”
Section: Introductionmentioning
confidence: 99%